Heavy-duty anti-corrosion coating containing polyurethane microcapsules, preparation method of heavy-duty anti-corrosion coating and coating
By using polyurethane microcapsules and polydopamine to coat sheet-like basalt scales in heavy anticorrosion coatings, combining epoxy resin and polyamide resin, the problems of prone to cracks and high VOCs emissions in traditional coatings are solved, and efficient anti-corrosion and Self-healing performance reduces environmental pollution.
Patent Information
- Application Number
- CN202411185278.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-17
AI Technical Summary
Traditional heavy anticorrosion coatings are prone to microcracks under external forces and environment, resulting in coating failure. In addition, VOCs emissions are high during the preparation process, pollute the environment, and the self-repair performance is difficult to ensure.
Use heavy anticorrosion coatings containing polyurethane microcapsules, and coat the sheet-shaped basalt scales and polyurethane oligomer microcapsules with both end groups of NCO through polydopamine, combining epoxy resin and polyamide resin to form an efficient anticorrosion coating. Reduce the VOCs content and add bentonite, zinc powder and steel slag shield powder to the coating to improve weathering and chemical resistance.
It realizes the long-term anti-corrosion life of the coating, improves the corrosion resistance and self-repair ability of the coating, reduces VOCs emissions, reduces environmental pollution, and enhances the adhesion and adhesion of the coating.
Smart Images

Figure CN119144205A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-corrosion coatings, and in particular relates to a heavy-duty anti-corrosion coating containing polyurethane microcapsules, a preparation method thereof and a coating. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] As a protective method with excellent performance and high protection efficiency, heavy-duty anti-corrosion coating systems have been widely used in harsh corrosive environments. However, during the service of traditional heavy-duty anti-corrosion coating systems, the coating will inevitably produce microcracks under the influence of external forces, environmental climate, etc. The expansion and spread of microcracks will eventually lead to coating failure, and after the coating is damaged, it is easy to become the source of corrosion, resulting in the failure of subsequent coating protection systems. If the cracks can be automatically repaired at the initial stage of formation - the microcrack stage, the potential harm is reduced and the corrosion resistance of the coating system is greatly improved.
[0004] In addition, the liquid coatings used to prepare heavy-duty anti-corrosion coatings have relatively high VOCs emissions, which cause great pollution to the environment and are not conducive to the protection of the ecological environment.
[0005] Most traditional self-repairing coatings require sufficient external stimulation (heat, light, etc.) to achieve self-repairing performance, which will result in the coating being unable to perform self-repairing behavior immediately after being damaged, affecting the coating performance, and the self-repairing performance is difficult to guarantee. Self-repairing coatings that do not require external stimulation usually have lower strength. Summary of the invention
[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a heavy-duty anti-corrosion coating containing polyurethane microcapsules, a preparation method thereof and a coating. The coating can effectively reduce the VOCs content, and the prepared coating has excellent weather resistance, chemical resistance and microcrack resistance, and has a long anti-corrosion life. It overcomes the problems of environmental pollution caused by high VOCs content in traditional heavy-duty anti-corrosion coating systems, coating failure caused by easy damage to the coating, cracking and powdering of the coating caused by insufficient weather resistance, etc.
[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0008] In a first aspect, the present invention provides a heavy-duty anticorrosive coating containing polyurethane microcapsules, including a primer, an intermediate paint and a topcoat, wherein:
[0009] The primer comprises component A and component B, wherein component A is composed of the following components by weight: 10-18 parts of epoxy resin; 8-15 parts of solvent; 2-6 parts of bentonite; 2-4 parts of microcapsules; 2-4 parts of polydopamine-coated flaky basalt flakes; 50-60 parts of zinc powder; 10-15 parts of steel slag shield powder; 0.5-1 part of soybean lecithin; component B is composed of the following components by weight: 15-25 parts of solvent; 70-90 parts of polyamide resin;
[0010] The intermediate paint comprises component A and component B, wherein component A is composed of the following components by weight: 8-15 parts of solvent; 2-4 parts of hydroxy acrylic resin; 15-25 parts of epoxy resin; 2-6 parts of bentonite; 0.2-0.5 parts of soybean lecithin; 0.5-3 parts of microcapsules; 0.5-2 parts of polydopamine-coated flaky basalt flakes; 50-60 parts of micaceous iron powder; 5-10 parts of titanium dioxide; 1-2 parts of carbon black; and component B is composed of the following components by weight: 15-25 parts of solvent; 70-90 parts of polyamide resin;
[0011] The topcoat comprises component A and component B. Component A consists of the following components in parts by mass: 8-15 parts of organosilicon-modified acrylic resin; 2-4 parts of organosilicon resin; 15-20 parts of hollow microspheres; 2-5 parts of polydopamine-coated flaky basalt flakes; 0.2-0.5 parts of titanium dioxide; 0.5-1.5 parts of soybean lecithin; 0.5-1.5 parts of fumed silica; 50-60 parts of solvent; 5-10 parts of catalyst; and component B consists of the following components in parts by mass: 80-100 parts of curing agent; and 8-12 parts of microcapsules.
[0012] In some embodiments, the heavy-duty anticorrosive coating containing polyurethane microcapsules includes a primer, an intermediate paint, and a topcoat, wherein:
[0013] The primer comprises component A and component B, wherein component A is composed of the following components by weight: 12-15 parts of epoxy resin; 10-13 parts of solvent; 3-5 parts of bentonite; 2-4 parts of microcapsules; 2-3 parts of polydopamine-coated flaky basalt flakes; 50-55 parts of zinc powder; 10-13 parts of steel slag shield powder; 0.5-0.8 parts of soybean lecithin; component B is composed of the following components by weight: 15-20 parts of solvent; 70-80 parts of polyamide resin;
[0014] The intermediate paint comprises component A and component B, wherein component A is composed of the following components by weight: 8-10 parts of solvent; 2-3 parts of hydroxy acrylic resin; 15-20 parts of epoxy resin; 2-5 parts of bentonite; 0.2-0.5 parts of soybean lecithin; 0.5-2 parts of microcapsules; 0.5-1 parts of polydopamine-coated flaky basalt flakes; 50-55 parts of micaceous iron powder; 6-10 parts of titanium dioxide; and 1-1.5 parts of carbon black; and component B is composed of the following components by weight: 15-25 parts of solvent; and 75-85 parts of polyamide resin.
[0015] The topcoat comprises component A and component B. Component A consists of the following components in parts by mass: 8-12 parts of organosilicon-modified acrylic resin; 2-3 parts of organosilicon resin; 17-20 parts of hollow microspheres; 2-4 parts of polydopamine-coated flaky basalt flakes; 0.2-0.4 parts of titanium dioxide; 0.5-1 parts of soybean lecithin; 0.7-1.2 parts of fumed silica; 50-55 parts of solvent; 6-10 parts of catalyst; and component B consists of the following components in parts by mass: 80-100 parts of curing agent; and 8-10 parts of microcapsules.
[0016] The primer is an epoxy zinc-rich primer, in which epoxy resin and polyamide resin are resin matrices and curing agents, and any common epoxy resin on the market can be used; the solvent is used as an active diluent to reduce the viscosity of the system while reducing the content of VOCs.
[0017] Bentonite as an additive can improve the suspension stability of the coating and prevent the coating from stratification and precipitation. At the same time, when bentonite comes into contact with the water medium, it will react and combine with the coating to improve the coating's water resistance, adhesion, strength and bonding.
[0018] Polydopamine-coated flaky basalt flakes are added as functional fillers. The polydopamine coating makes the basalt flakes have excellent photothermal conversion efficiency and performance. The photothermal performance makes the coating temperature rise to accelerate the self-repair speed of the coating, and accelerate the reaction speed of the polyurethane oligomer with NCO terminal groups in the microcapsule with the aqueous medium, preventing the slow self-repair speed from causing the failure to hinder the diffusion of the corrosive medium in time, resulting in coating failure.
[0019] The use of flaky basalt flakes, which take advantage of the more complex paths of flaky materials, increases the difficulty of diffusion of corrosive media in the coating. As an inorganic filler with excellent anti-corrosion performance, basalt flakes can greatly improve the anti-corrosion performance of the coating, and utilize physical and chemical synergy to improve the corrosion resistance of the coating. Polydopamine modification improves the binding performance of basalt flakes in the organic matter of the coating, improves the adhesion of the coating, and improves the density of the coating.
[0020] Zinc powder is used as a filler for cathodic protection. It protects the substrate through cathodic protection and provides corrosion resistance to the coating.
[0021] As a new type of low-cost filler, steel slag shield powder can effectively reduce the cost of coatings, while improving the anti-corrosion performance and enhancing the wear resistance and strength of the coating.
[0022] Utilize the surface activity of soybean lecithin to shorten the heating time, prevent pigment precipitation, increase brightness, avoid stratification, and increase coverage and leveling, dispersibility, and wettability.
[0023] The intermediate paint is an epoxy anti-rust intermediate paint, in which micaceous iron powder, titanium dioxide and black pigment are added as pigments, the black pigment is carbon black, and the micaceous iron powder can improve the bonding strength between the intermediate paint and the topcoat and primer, and improve the hiding power of the intermediate paint.
[0024] Titanium dioxide has excellent light scattering properties and can scatter incident light evenly in all directions, making the coating surface look smooth and uniform and improving the gloss of the coating. Titanium dioxide has good protection against ultraviolet rays, which can reduce the penetration of ultraviolet rays, reduce the possibility of coating aging, fading and yellowing, and enhance the weather resistance of the coating. Increase the durability of the coating: Titanium dioxide can form a dense protective film in the coating, improve the wear resistance, chemical resistance and weather resistance of the coating, and extend the service life of the coating.
[0025] Carbon black can enhance the wear resistance of coatings, has excellent UV absorption ability, enhances the UV resistance of coatings, prevents yellowing and aging of coatings, enhances the corrosion resistance of coatings, and improves weather resistance.
[0026] In the topcoat, the hollow microspheres are hollow ceramic microspheres, which have a very light density, high porosity and good heat resistance, which allows them to maintain stability under high temperature and high pressure. In addition, the surface of the hollow glass microspheres is smooth, which makes it easy to disperse and mix in the coating.
[0027] Hollow microspheres can improve the adhesion of paint. Adding a certain amount of hollow glass microspheres to the paint can increase the adhesion of the coating. Because of its high porosity and light density, hollow glass microspheres can form a uniform distribution in the paint, which plays a good role in enhancing the adhesion of the coating. At the same time, it can increase the durability of the paint and reduce the density of the paint.
[0028] In some embodiments, the microcapsule includes a shell and a core, the shell is made of a photocurable resin, and the core is made of a polyurethane oligomer with NCO groups at both ends.
[0029] The characteristic of polyurethane oligomers with NCO groups at both ends of the polymer is that both ends are reactive isocyanate groups, and the molecular weight is usually around 1500.
[0030] The preparation method of the polyurethane oligomer with NCO groups at both ends is as follows: using polyethylene glycol (PEG) with a molecular weight (400-1000), 3-dimethylamino-1,2-propylene glycol (DAP), isophorone diisocyanate (IPID), and N,N-dimethylformamide as raw materials, polycondensing under the catalysis of stannous octoate to synthesize the polyurethane oligomer with NOC groups at both ends.
[0031] Preferably, the photocurable resin is polyurethane acrylic resin.
[0032] As a functional filler, microcapsules can greatly improve the performance of heavy-duty anti-corrosion coatings. When the corrosive medium penetrates the coating, the polyurethane shell material of the microcapsules hydrolyzes to release the polyurethane oligomers with NCO at both ends in the core material. The core material reacts and solidifies when in contact with the corrosive medium, promptly consuming and preventing the penetration of the corrosive medium. In addition, the polyurethane oligomer core material with NCO at both ends can provide the coating with self-repairing properties for microcracks, thereby improving the performance and life of the heavy-duty anti-corrosion coating system.
[0033] Preferably, the method for preparing the microcapsules comprises the following steps:
[0034] Dissolving a photocurable resin, a polyurethane oligomer with NCO groups at both ends, and a photoinitiator in an organic solvent in proportion to obtain an oil phase;
[0035] adding an aqueous solution of an emulsifier to the oil phase to obtain an oil-in-water emulsion;
[0036] The emulsion is left to stand to evaporate the organic solvent, and then light-cured to obtain microcapsules.
[0037] Further preferably, the mass ratio of the photocurable resin, the polyurethane oligomer having NCO groups at both ends and the photoinitiator is 15-25:10-20:1-3.
[0038] More preferably, in the aqueous solution of the emulsifier, the concentration of the emulsifier is 1-2 wt %.
[0039] More preferably, the emulsifier is a polyvinyl alcohol aqueous dispersion; and the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone.
[0040] Further preferably, the organic solvent is dichloromethane; in the emulsion, the volume ratio of oil to water is 1:4-7.
[0041] In some embodiments, the method for preparing the polydopamine-coated flaky basalt scales comprises the following steps:
[0042] The flaky basalt flakes are ultrasonically dispersed in water, dopamine hydrochloride and tris(hydroxymethyl)aminomethane are added thereto, and the mixture is stirred and reacted at 20-35° C. for 1.5-2.5 hours to obtain the product.
[0043] Dopamine hydrochloride and tris(hydroxymethylaminomethane) are the raw materials for preparing polydopamine on the surface of scales, and tris(hydroxymethylaminomethane) is a catalyst.
[0044] Preferably, the concentration of flaky basalt flakes in water is 1-5 g / L; the concentration of dopamine hydrochloride in water is 0.5-2 g / L; and the concentration of tris(hydroxymethyl)aminomethane in water is 0.5-2 g / L.
[0045] In some embodiments, the solvent in the primer is propylene glycol methyl ether acetate; the solvent in the intermediate paint is 1,6-hexanediol diacrylate; and the solvent in the topcoat is 1,6-hexanediol diacrylate.
[0046] In some embodiments, the catalyst in the topcoat is bis(p-chlorobenzyl) peroxide.
[0047] In some embodiments, in the primer, the mass ratio of component A to component B is 15-25:1; in the intermediate paint, the mass ratio of component A to component B is 5-15:1; in the topcoat, the mass ratio of component A to component B is 5-15:1.
[0048] In a second aspect, the present invention provides a method for preparing the heavy-duty anticorrosive coating containing polyurethane microcapsules, comprising the following steps:
[0049] The preparation method of the primer comprises: mixing component A and component B of the primer according to a set mass ratio and stirring at a high speed until they are completely uniform, so as to obtain a primer coating;
[0050] The preparation method of the intermediate paint is: mixing component A and component B of the intermediate paint according to a set mass ratio and stirring at a high speed until they are completely uniform, so as to obtain an intermediate paint coating;
[0051] The preparation method of the topcoat comprises: mixing component A and component B of the topcoat according to a set mass ratio and stirring at a high speed until the mixture is completely uniform, so as to obtain a topcoat coating.
[0052] In some embodiments, in the primer, the mass ratio of component A to component B is 15-25:1, preferably 20:1;
[0053] In the intermediate paint, the mass ratio of component A to component B is 8-12:1, preferably 10:1;
[0054] In the topcoat, the mass ratio of component A to component B is 8-12:1, preferably 10:1.
[0055] In a third aspect, the present invention provides a heavy-duty anti-corrosion coating containing polyurethane microcapsules, comprising a base layer, an intermediate layer and a surface layer, wherein the base layer is prepared from the primer; the intermediate layer is prepared from the intermediate paint; and the surface layer is prepared from the topcoat.
[0056] In some embodiments, the thickness of the bottom layer is 80-100 μm; the thickness of the middle layer is 100-120 μm; and the thickness of the surface layer is 100-120 μm.
[0057] In a fourth aspect, the present invention provides a method for preparing the heavy-duty anticorrosion coating containing polyurethane microcapsules, comprising the following steps:
[0058] After cleaning the substrate, spray the primer evenly on the surface of the substrate, dry and solidify to obtain the base layer;
[0059] Spray the intermediate paint evenly on the surface of the base layer, and after drying and curing, obtain the intermediate layer;
[0060] The topcoat is evenly sprayed on the surface of the middle layer, and after drying and curing, a heavy anti-corrosion coating is obtained.
[0061] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0062] The active diluent used in the coating of the present invention will participate in the curing reaction of the resin, so the organic solvent has been basically eliminated by the reaction, so that the VOCs content of the coating is low, and the amount of VOCs released into the environment after the coating is prepared is small, which is beneficial to reducing environmental pollution.
[0063] Adding light-cured polyurethane microcapsules to coatings can effectively improve the anti-corrosion performance and the service life of the coating system.
[0064] The photocuring method is used to prepare functional microcapsules, which is fast, efficient and simple. The prepared microcapsules have better coating properties and more uniform sizes.
[0065] Adding polydopamine-coated basalt flakes to the coating can improve the density of the coating system, increase the penetration path of the corrosive medium, and improve the long-term heavy-duty anti-corrosion performance.
[0066] Microcapsules are added to three layers of coating (base layer, middle layer and surface layer), which can greatly improve the heavy-duty anti-corrosion performance. When the corrosive medium penetrates the surface layer, middle layer and base layer, the polyurethane shell material of the microcapsule hydrolyzes to release the polyurethane oligomers with NCO at both ends in the core material. The core material reacts and solidifies when in contact with the corrosive medium, promptly consuming and preventing the penetration of the corrosive medium. In addition, the polyurethane oligomer core material with NCO at both ends can provide the coating with self-repairing properties for microcracks, thereby improving the performance and life of the heavy-duty anti-corrosion coating system.
[0067] A polyurethane oligomer with NCO groups at both ends is used as the core material. Since the polyurethane oligomer with NCO groups at both ends has a molecular weight between small monomer molecules and large monomer molecules, it can be well dispersed and coated, and at the same time has a higher molecular weight than the traditional monomer isocyanate. When in contact with the aqueous medium, the molecular weight increases more rapidly during the reaction, the reaction efficiency is faster, the self-repairing behavior can be completed faster, the diffusion of the aqueous medium is hindered, and better and more excellent self-repairing performance is achieved.
[0068] Polydopamine-coated flaky basalt flakes are used as functional additives. Polydopamine modification improves the bonding force between inorganic fillers and organic coatings, while giving the coatings excellent photothermal properties. The polydopamine coating makes the basalt flakes have excellent photothermal conversion efficiency and performance, and the photothermal properties make the coating temperature rise to accelerate the self-repair speed of the coating, and accelerate the reaction speed of the polyurethane oligomer with NCO end groups in the microcapsule with the aqueous medium, preventing the slow self-repair speed from causing the failure of the coating to prevent the diffusion of the corrosive medium from being blocked in time.
[0069] Flaky basalt flakes are used, and the flaky materials have more complex paths, which increases the difficulty of diffusion of corrosive media in the coating. Basalt flakes, as inorganic fillers with excellent anti-corrosion properties, can greatly improve the anti-corrosion properties of the coating, and utilize physical and chemical synergy to improve the corrosion resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0071] Figure 1 It is a schematic structural diagram of a heavy-duty anti-corrosion coating system according to an embodiment of the present invention.
[0072] Among them, 1-matrix; 2-bottom layer; 3-middle layer; 4-surface layer. DETAILED DESCRIPTION
[0073] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0074] The present invention will be further described below in conjunction with the embodiments.
[0075] Example 1
[0076] Heavy-duty anticorrosive coating containing polyurethane microcapsules, including primer, intermediate paint and topcoat, wherein:
[0077] The primer includes component A and component B, and the mass ratio of component A to component B is 20:1;
[0078] Component A is composed of the following components by mass: 14 parts of epoxy resin; 11 parts of solvent propylene glycol methyl ether acetate; 4 parts of bentonite; 2.5 parts of microcapsules; 2.5 parts of polydopamine-coated flaky basalt flakes; 55 parts of zinc powder; 10.4 parts of steel slag shield powder; and 0.6 parts of soybean lecithin.
[0079] Component B is composed of the following components by mass: 20 parts of solvent propylene glycol methyl ether acetate; and 80 parts of polyamide resin.
[0080] The preparation method of the primer comprises: mixing the A component and the B component of the primer in a mass ratio of 20:1 and stirring at a high speed until the mixture is completely uniform, so as to obtain the primer coating.
[0081] The intermediate paint includes component A and component B, and the mass ratio of component A to component B is 10:1;
[0082] Component A is composed of the following components by mass: 10 parts of solvent 1,6-hexanediol diacrylate; 2.5 parts of hydroxy acrylic resin; 19.8 parts of epoxy resin; 3 parts of bentonite; 0.3 parts of soybean lecithin; 1 part of microcapsule; 1 part of polydopamine-coated flaky basalt scale; 53 parts of micaceous iron powder; 8 parts of titanium dioxide; 1.4 parts of carbon black;
[0083] Component B is composed of the following components by mass: 20 parts of solvent 1,6-hexanediol diacrylate; and 80 parts of polyamide resin.
[0084] The preparation method of the intermediate paint is: mixing the A component and the B component of the intermediate paint in a mass ratio of 10:1 and stirring at a high speed until they are completely uniform, so as to obtain the intermediate paint coating.
[0085] The topcoat comprises component A and component B, wherein the mass ratio of component A to component B is 10:1; component A is composed of the following components by mass: 10 parts of silicone-modified acrylic resin; 2.5 parts of silicone resin; 19.8 parts of hollow microspheres; 3 parts of polydopamine-coated flaky basalt flakes; 0.3 parts of titanium dioxide; 1 part of soybean lecithin; 1 part of fumed silica; 53 parts of solvent 1,6-hexanediol diacrylate; 8 parts of catalyst bis(p-chlorobenzyl) peroxide;
[0086] Component B is composed of the following components by mass: 90 parts of 3390 curing agent and 10 parts of microcapsules.
[0087] The preparation method of the topcoat comprises: mixing component A and component B of the topcoat in a mass ratio of 10:1 and stirring at a high speed until the mixture is completely uniform, thereby obtaining a topcoat coating.
[0088] The method for preparing a polyurethane oligomer with NOC groups at both ends comprises the following steps:
[0089] According to the ingredient ratio, PEG and DAP are first dissolved in half of DMF, placed in a dry three-necked round-bottom flask, and mechanically stirred evenly (about 10 minutes); IPDI and stannous octoate are added under nitrogen protection; the entire device is placed in a 65°C oil bath for heating, and stirred until the -NCO content reaches the theoretical content (titration is performed using di-n-butylamine titration method), about 45 minutes, to obtain a -NCO-terminated prepolymer (DPU), to which the remaining N,N-dimethylformamide DMF is added for dilution, slowly stirred and cooled to 40°C.
[0090] The molar ratio of PEG, DAP, IPDI, DMF and stannous octoate is 1:1:5:5:0.05-0.2.
[0091] The synthesis mechanism diagram is as follows:
[0092]
[0093] The preparation method of microcapsules is as follows:
[0094] The microcapsule comprises a shell material and a core material, wherein the shell material is a light-curable resin and the core material is an isocyanate; the light-curable resin is a polyurethane acrylic resin; and the isocyanate is an oligomer of terminal isocyanate;
[0095] 1) dissolving and dispersing 3 g of a photocurable resin, 3 g of a polyurethane oligomer having NCO end groups, and 0.06 g of a photoinitiator, 2-hydroxy-2-methyl-1-phenyl-1-propanone, in dichloromethane to obtain an oil phase;
[0096] 2) adding an aqueous solution of an emulsifier to the oil phase, wherein the emulsifier is a polyvinyl alcohol aqueous dispersion, the concentration of the emulsifier is 1.5 wt %, the mass ratio of oil to water is 1:5, and stirring at a high speed of 500 r / min to obtain an oil-in-water emulsion;
[0097] 3) The oil-in-water emulsion was stirred at 30° C. to volatilize the organic solvent, and then placed under a UV light source for photocuring for 15 minutes to obtain polyurethane microcapsules.
[0098] The preparation method of the heavy-duty anti-corrosion coating comprises the following steps:
[0099] 1) Spray the epoxy zinc-rich primer onto the outer surface of the Q235 carbon steel substrate with a thickness of 80 μm;
[0100] 2) Spray the anti-rust intermediate paint onto the dried and cured primer surface with a thickness of 100 μm;
[0101] 3) Spraying polysiloxane topcoat onto the surface of the dried and cured intermediate paint coating with a thickness of 100 μm;
[0102] 4) After the above layers are dried, a heavy-duty anti-corrosion coating system is obtained, and its performance data is shown in Table 1.
[0103] Example 2
[0104] The composition and preparation method of the primer, intermediate paint and topcoat are the same as those in Example 1.
[0105] The preparation method of the heavy-duty anti-corrosion coating comprises the following steps:
[0106] 1) Spray the epoxy zinc-rich primer onto the outer surface of the Q235 carbon steel substrate with a thickness of 100 μm;
[0107] 2) Spray the anti-rust intermediate paint onto the dried and cured primer surface with a thickness of 120 μm;
[0108] 3) Spraying polysiloxane topcoat onto the surface of the dried and cured intermediate paint coating with a thickness of 100 μm;
[0109] 4) After the above layers are dried, a heavy-duty anti-corrosion coating system is obtained, and its performance data is shown in Table 1.
[0110] Example 3
[0111] The composition and preparation method of the primer, intermediate paint and topcoat are the same as those in Example 1.
[0112] The preparation method of the heavy-duty anti-corrosion coating comprises the following steps:
[0113] 1) Spraying zinc-rich epoxy onto the outer surface of the Q235 carbon steel substrate with a thickness of 100 μm;
[0114] 2) Spray the anti-rust intermediate paint onto the dried and cured primer surface with a thickness of 120 μm;
[0115] 3) Spraying polysiloxane topcoat onto the dried and cured surface of the intermediate paint coating with a thickness of 120 μm;
[0116] 4) After the above layers are dried, a heavy-duty anti-corrosion coating system is obtained, and its performance data is shown in Table 1.
[0117] Comparative Example 1
[0118] The difference from Example 1 is that the polydopamine-coated basalt flakes are omitted in the primer, the intermediate paint and the topcoat, and the rest are the same as Example 1. The performance data of the heavy-duty anticorrosive coating system is shown in Table 1.
[0119] Comparative Example 2
[0120] The difference from Example 1 is that the microcapsules and polydopamine-coated basalt flakes are omitted in the primer, the intermediate paint and the topcoat, and the rest are the same as Example 1. The performance data of the heavy anticorrosive coating system is shown in Table 1.
[0121] Comparative Example 3
[0122] The difference from Example 1 is that the microcapsules are omitted in the primer, the intermediate paint and the topcoat, and the rest is the same as Example 1. The performance data of the heavy anticorrosive coating system is shown in Table 1.
[0123] Table 1 Performance data of heavy-duty anti-corrosion coating
[0124]
[0125] Note: The qualified standard for chemical resistance is: the coating does not rust, bubble, crack, peel, change color no more than 2 levels, and lose gloss no more than 2 levels; the suitable standard for aging resistance is: the coating does not rust, bubble, crack, peel, powder, change color no more than 2 levels, and lose gloss no more than 2 levels.
[0126] The salt spray corrosion resistance test is carried out according to GB / T 10125 standard to test the corrosion resistance. The electrochemical impedance spectroscopy (EIS) test of the coating system is carried out using testing and analysis instruments such as AUTOLAB electrochemical workstation. The adhesion grade is tested according to ISO2409 standard. The adhesion is tested using GB / T 5210 standard. The acid and alkali resistance is tested according to GB1763-79 (89) standard. The artificial weathering resistance of the coating is tested for 3000 hours according to GB / T 1865-2009.
[0127] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A heavy-duty anticorrosive coating containing polyurethane microcapsules, characterized in that: Including primer, intermediate paint and topcoat, among which, The primer comprises component A and component B, wherein component A is composed of the following components by weight: 10-18 parts of epoxy resin; 8-15 parts of solvent; 2-6 parts of bentonite; 2-4 parts of microcapsules; 2-4 parts of polydopamine-coated flaky basalt flakes; 50-60 parts of zinc powder; 10-15 parts of steel slag shield powder; 0.5-1 part of soybean lecithin; component B is composed of the following components by weight: 15-25 parts of solvent; 70-90 parts of polyamide resin; The intermediate paint comprises component A and component B, wherein component A is composed of the following components by weight: 8-15 parts of solvent; 2-4 parts of hydroxy acrylic resin; 15-25 parts of epoxy resin; 2-6 parts of bentonite; 0.2-0.5 parts of soybean lecithin; 0.5-3 parts of microcapsules; 0.5-2 parts of polydopamine-coated flaky basalt flakes; 50-60 parts of micaceous iron powder; 5-10 parts of titanium dioxide; 1-2 parts of carbon black; and component B is composed of the following components by weight: 15-25 parts of solvent; 70-90 parts of polyamide resin; The topcoat comprises component A and component B. Component A consists of the following components in parts by mass: 8-15 parts of organosilicon-modified acrylic resin; 2-4 parts of organosilicon resin; 15-20 parts of hollow microspheres; 2-5 parts of polydopamine-coated flaky basalt flakes; 0.2-0.5 parts of titanium dioxide; 0.5-1.5 parts of soybean lecithin; 0.5-1.5 parts of fumed silica; 50-60 parts of solvent; 5-10 parts of catalyst; and component B consists of the following components in parts by mass: 80-100 parts of curing agent; and 8-12 parts of microcapsules.
2. The heavy-duty anticorrosion coating containing polyurethane microcapsules according to claim 1, characterized in that: Including primer, intermediate paint and topcoat, among which, The primer comprises component A and component B, wherein component A is composed of the following components by weight: 12-15 parts of epoxy resin; 10-13 parts of solvent; 3-5 parts of bentonite; 2-4 parts of microcapsules; 2-3 parts of polydopamine-coated flaky basalt flakes; 50-55 parts of zinc powder; 10-13 parts of steel slag shield powder; 0.5-0.8 parts of soybean lecithin; component B is composed of the following components by weight: 15-20 parts of solvent; 70-80 parts of polyamide resin; The intermediate paint comprises component A and component B, wherein component A is composed of the following components by weight: 8-10 parts of solvent; 2-3 parts of hydroxy acrylic resin; 15-20 parts of epoxy resin; 2-5 parts of bentonite; 0.2-0.5 parts of soybean lecithin; 0.5-2 parts of microcapsules; 0.5-1 parts of polydopamine-coated flaky basalt flakes; 50-55 parts of micaceous iron powder; 6-10 parts of titanium dioxide; and 1-1.5 parts of carbon black; and component B is composed of the following components by weight: 15-25 parts of solvent; and 75-85 parts of polyamide resin. The topcoat comprises component A and component B. Component A consists of the following components in parts by mass: 8-12 parts of organosilicon-modified acrylic resin; 2-3 parts of organosilicon resin; 17-20 parts of hollow microspheres; 2-4 parts of polydopamine-coated flaky basalt flakes; 0.2-0.4 parts of titanium dioxide; 0.5-1 parts of soybean lecithin; 0.7-1.2 parts of fumed silica; 50-55 parts of solvent; 6-10 parts of catalyst; and component B consists of the following components in parts by mass: 80-100 parts of curing agent; and 8-10 parts of microcapsules.
3. The heavy-duty anticorrosion coating containing polyurethane microcapsules according to claim 1 or 2, characterized in that: The microcapsule comprises a shell and a core, the shell is made of a photocurable resin, and the core is made of a polyurethane oligomer with NCO groups at both ends; Preferably, the photocurable resin is polyurethane acrylic resin.
4. The heavy-duty anticorrosion coating containing polyurethane microcapsules according to claim 3, characterized in that: The preparation method of the microcapsule comprises the following steps: Dissolving a photocurable resin, a polyurethane oligomer with NCO groups at both ends, and a photoinitiator in an organic solvent in proportion to obtain an oil phase; adding an aqueous solution of an emulsifier to the oil phase to obtain an oil-in-water emulsion; After the emulsion is allowed to stand to volatilize the organic solvent, it is light-cured to obtain microcapsules; Preferably, the mass ratio of the photocurable resin, the polyurethane oligomer with NCO groups at both ends and the photoinitiator is 15-25:10-20:1-3; Preferably, in the aqueous solution of the emulsifier, the concentration of the emulsifier is 1-2 wt %; Preferably, the emulsifier is a polyvinyl alcohol aqueous dispersion; the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone; Preferably, the organic solvent is dichloromethane; in the emulsion, the volume ratio of oil to water is 1:4-7.
5. The heavy-duty anticorrosion coating containing polyurethane microcapsules according to claim 1 or 2, characterized in that: The preparation method of the polydopamine-coated flaky basalt scales comprises the following steps: Ultrasonic dispersion of flaky basalt flakes in water, adding dopamine hydrochloride and tris(hydroxymethyl)aminomethane thereto, stirring and reacting at 20-35° C. for 1.5-2.5 h, to obtain; Preferably, the concentration of flaky basalt flakes in water is 1-5 g / L; the concentration of dopamine hydrochloride in water is 0.5-2 g / L; and the concentration of tris(hydroxymethyl)aminomethane in water is 0.5-2 g / L.
6. The heavy-duty anticorrosion coating containing polyurethane microcapsules according to claim 1 or 2, characterized in that: The solvent in the primer is propylene glycol methyl ether acetate; the solvent in the intermediate paint is 1,6-hexanediol diacrylate; the solvent in the topcoat is 1,6-hexanediol diacrylate; Preferably, the catalyst in the topcoat is bis(p-chlorobenzyl) peroxide; Preferably, in the primer, the mass ratio of component A to component B is 15-25:1; in the intermediate paint, the mass ratio of component A to component B is 5-15:1; in the topcoat, the mass ratio of component A to component B is 5-15:
1.
7. The method for preparing the heavy-duty anticorrosive coating containing polyurethane microcapsules according to any one of claims 1 to 6, characterized in that: The steps include: The preparation method of the primer comprises: mixing component A and component B of the primer according to a set mass ratio and stirring at a high speed until they are completely uniform, thereby obtaining a primer coating; The preparation method of the intermediate paint is: mixing component A and component B of the intermediate paint according to a set mass ratio and stirring at a high speed until they are completely uniform, thereby obtaining an intermediate paint coating; The preparation method of the topcoat comprises: mixing component A and component B of the topcoat according to a set mass ratio and stirring at a high speed until the mixture is completely uniform, so as to obtain a topcoat coating.
8. A heavy-duty anticorrosion coating containing polyurethane microcapsules, characterized in that: The invention comprises a bottom layer, an intermediate layer and a surface layer, wherein the bottom layer is prepared from the primer described in claim 1; the intermediate layer is prepared from the intermediate paint described in claim 1; and the surface layer is prepared from the top paint described in claim 1.
9. The heavy-duty anticorrosion coating containing polyurethane microcapsules according to claim 8, characterized in that: The thickness of the bottom layer is 80-100 μm; the thickness of the middle layer is 100-120 μm; and the thickness of the surface layer is 100-120 μm.
10. The method for preparing the heavy-duty anticorrosion coating containing polyurethane microcapsules according to claim 8 or 9, characterized in that: The steps include: After cleaning the substrate, spray the primer evenly on the surface of the substrate, dry and solidify to obtain the base layer; Spray the intermediate paint evenly on the surface of the base layer, and after drying and curing, obtain the intermediate layer; The topcoat is evenly sprayed on the surface of the middle layer, and after drying and curing, a heavy anti-corrosion coating is obtained.
Citation Information
Patent Citations
Self-repairing microcapsule used for metal anticorrosive paint and preparation method thereof
CN107312140A
Self-repairing anticorrosive outdoor building graphene coating and preparation method thereof
CN108912870A
Self-repairing high-durability anticorrosive composite coating and preparation method thereof
CN110358406A
Self-repairing anticorrosive paint containing polyaniline double-layer microcapsules
CN115505332A
Moisture-curable self-repairing epoxy anticorrosive paint and preparation method thereof
CN117586685A
Cited By
Anti-icing coating, functional layer, multifunctional coating, preparation method and application
CN120842987A
